Understanding Pre-Service Elementary Teachers’ Expectations for a Culture- Integrated Learning Management System - Ardiansyah, Amalia Rizki; Murjainah; Joronavalona, Rasamimanana; Ame, Ibrahim Pandu; Rashid, Salman (Jurnal Prima Edukasia, 2025)
The increasing demand for learning platforms that effectively integrate local wisdom and cultural content necessitates an understanding of user expectations, especially among pre-service elementary teachers (PSETs) who will utilize these tools. This study aims to identify PSET students' expectations for the design and implementation of a culture-integrated Learning Management System (LMS) and to explore the challenges they encounter in its use. This study employs a mixed-methods approach, collecting data through a survey administered to 30 PSETs and in-depth interviews with four participants (two male and two female) from the Elementary School Teacher Education Study Program at Yogyakarta State University. The findings reveal seven main aspects that affect the LMS user experience: ease of access, clarity of navigation, material management, speed of assignment collection, technical problems, timely notification, and discussion features. The survey and interview results indicate that technical issues and accessibility remain the primary challenges, while aspects of material management and speed of assignment submission receive positive ratings. Students emphasize the importance of interactive features, culturally relevant content, and an improved LMS interface design. This study concludes that continuous improvements in accessibility, technical support, and the strategic integration of culturally relevant content are crucial for enhancing the learning experience of PSETs. These findings contribute to the body of knowledge by providing specific, empirically driven design and implementation recommendations for developers and educators seeking to create culturally sensitive and effective digital learning environments for future elementary school teachers.